Natural Resistance of Rattan Species from Sumatra Against Subterranean Termite and Its Relation to Chemical Properties (Ketahanan Alami Rotan Asal Sumatra terhadap Rayap Tanah dan Hubungannya dengan Sifat Kimia) - Wa OM Arsyad; Lisna Efiyanti; Titi Kalima (Masyarakat Peneliti Kayu Indonesia, 2018)
The main problem of rattan utilization was the ravages of destructive organisms attack. The objective of this study was to determine the natural resistance of rattan species from Sumatra against subterranean termites and its relation with the chemical characteristics of rattan. All samples were tested for resistance to subterranean termite and its chemical characteristics according to the Indonesian National Standard. Observations, percentage weight loss, termite survival and degree of attack were determined. Results showed that Calamus insignis, C. holttumii, Daemonorps verticillaris, and D. longipes included in very resistant (Class I). Korthalsia flagellaris, C. zonatus, C. laevigatus, D. sepals, C. spectatissimus, C. rugosus, and C. oleyanus included in resistance class II. Furthermore, D. micracantha included in the class of moderate resistance (class III). The cellulose content has no significant correlation (P>0.01), and lignin has a significant negative correlation (P<0.01) to the weight loss, termite survival and the degree of attack. Rattan that has resistance class I and II can be utilized as raw material of furniture and crafts, while rattan which have resistance class III require preservation treatment to extend its service life.